2002
DOI: 10.1002/mrm.10122
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of adiabatic fast passage for steady laminar and turbulent flows

Abstract: Adiabatic fast passage (AFP) is used in noninvasive quantitative perfusion experiments to invert (or label) arterial spins. Continuous arterial spin labeling (CASL) experiments conducted in vivo often assume the inversion efficiency based on the labeling field and steady flow conditions, without direct verification. In practice, the labeling field used in CASL is often amplitude-and duty cycle-limited due to hardware or specific absorption rate constraints. In this study, the effects of the labeling field ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…In a recent study (36), investigators measured the continuous labeling efficiency in a saline flow phantom by using the single-section approach. The results showed an efficiency of 0.85 for a mean flow velocity of 26.4 cm/sec with 2.5- With an approximate 7% increase in efficiency by using a gradient of 1.6 instead of 2.5 mT/m, the predicted efficiency with the imaging parameters used in our experiments will be 0.91, which is a very close match with our assumption.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study (36), investigators measured the continuous labeling efficiency in a saline flow phantom by using the single-section approach. The results showed an efficiency of 0.85 for a mean flow velocity of 26.4 cm/sec with 2.5- With an approximate 7% increase in efficiency by using a gradient of 1.6 instead of 2.5 mT/m, the predicted efficiency with the imaging parameters used in our experiments will be 0.91, which is a very close match with our assumption.…”
Section: Discussionmentioning
confidence: 99%
“…First, the velocity dependence of the adiabatic condition introduces variability in the degree of inversion obtained by a given RF pulse with velocity fluctuations. As indicated by others (16,19,17,18), appropriate choice of gradient magnitude and H 1 strength will minimize this effect, although at the expense of greater specific absorption rate.…”
Section: Discussionmentioning
confidence: 92%
“…Formulations for optimization of the continuous arterial spin labeling experiment have been presented previously for both the single (15) and double (16) coil experiments, providing general guidelines for choice of the adiabatic slice selection gradient, RF transmitter power and RF offset frequency for optimizing the inversion process, and minimizing the RF power required, and thus specific absorption rate (17,18). Using numerical solutions to the modified Bloch equations, Maccotta et al (19) indicated that measured adiabatic efficiencies in humans approach simulated levels, provided that one accounts for T 1 relaxation occurring during vascular transit periods.…”
Section: Introductionmentioning
confidence: 99%
“….n. [7] We assume that the magnetization is at equilibrium at the onset of inversion, M(0) ϭ M 0 ϭ (0, 0, M 0 ). The number of time steps of the simulations was increased until the results were stable, and a decrease in the step size yielded changes in the efficiency prediction of Ͻ0.05%.…”
Section: Theorymentioning
confidence: 99%
“…In the present work, we investigated the influence of a nonlinearity of the frequency offset using a local magnetic field gradient coil (12) on ␣. We also addressed the differences between laminar and plug flow (7), and the realistic behavior of the bloodflow velocity during the cardiac cycle (8).…”
mentioning
confidence: 99%